Experimental and Computational Study on the Reaction Pathways of Diradical Intermediates Formed from Myers‐Saito Cyclization of Maleimide‐Based Enediynes. Issue 12 (29th October 2020) - Lu, Haotian; Zhang, Mengsi; Li, Baojun; Ma, Hailong; Wang, Wenbo; Ding, Yun; Li, Xinxin; Hu, Aiguo
Abstract: Great efforts have been dedicated to studying the thermal‐induced Myers‐Saito cyclization (MSC) of enyne‐allene as the resulting diradicals hold significant potential in various fields, especially in antitumor applications. Besides abstracting hydrogen from DNA backbone and further inducing tumor cell death, the diradicals might react through multiple pathways and lose their efficiency in antitumor applications. The in‐depth understanding of the reaction pattern of these highly reactive diradical intermediates will provide clear guidelines for the design of new enyne‐allene with high antitumor potency. Herein, we report detailed studies to reveal the reaction mechanism of ketal‐conjugated enediynes, which are hydrolyzed and tautomerized into enyne‐allene structures in acidic condition and produce diradicals through MSC. Further 1, 3‐hydrogen atom transfer (HAT)/6‐endo cyclization to yield pyran‐type product or 5‐endo cyclization/1, 4‐HAT to yield furan‐type product were confirmed and rationalized through computational studies. The proposed reaction pathways were further verified with deuterium labeling experiments. Based on these new findings, a new enediyne with asymmetric structure and tertbutyl group to block the HAT process was synthesized, which demonstrated much higher cytotoxicity against the HeLa cell line with a half inhibition concentration (IC50 value) down to submicromolar level. Abstract : Detailed studies to reveal the reaction mechanism of ketal‐conjugated enediynes, which are hydrolyzed and tautomerized into enyne‐allene structures under acidic conditions and produce diradicals through Myers‐Saito cyclization are presented.